2021
DOI: 10.14309/ajg.0000000000001237
|View full text |Cite
|
Sign up to set email alerts
|

Persistently High Rate of Venous Thromboembolic Disease in Inflammatory Bowel Disease: A Population-Based Study

Abstract: INTRODUCTION: Venous thromboembolism (VTE) is known to be increased in inflammatory bowel disease (IBD). We aimed to determine whether rates of VTE in IBD have reduced over the past 30 years. METHODS: We used the population-based University of Manitoba IBD Epidemiology Database (1984–2018) to determine the incidence of VTE in IBD and the incidence rate ratio vs matched controls. In persons with IBD with and without VTE, we assessed for variables that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…In addition to the high rate of morbidity associated with VTE, as well as the large economic burden, prior data have shown an increased risk of mortality as a result of VTE 34 . In our study, we found that among all patients hospitalised with IBD, the presence of a VTE increased the odds of mortality by more than twofold, which is similar to findings from the Manitoba cohort 14 . Furthermore, individuals who had a VTE during hospitalisation had a higher risk of mortality if they were older (>80 years old), male, had colorectal surgery or flexible sigmoidoscopy/colonoscopy during hospitalisation, or had Clostridioides difficile .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition to the high rate of morbidity associated with VTE, as well as the large economic burden, prior data have shown an increased risk of mortality as a result of VTE 34 . In our study, we found that among all patients hospitalised with IBD, the presence of a VTE increased the odds of mortality by more than twofold, which is similar to findings from the Manitoba cohort 14 . Furthermore, individuals who had a VTE during hospitalisation had a higher risk of mortality if they were older (>80 years old), male, had colorectal surgery or flexible sigmoidoscopy/colonoscopy during hospitalisation, or had Clostridioides difficile .…”
Section: Discussionsupporting
confidence: 88%
“…In our study, despite advances in medical knowledge, and increasing awareness of the risk of VTE in IBD as highlighted in the 2014 Canadian Association of Gastroenterology's consensus statement, we found that the rate of VTE among all hospitalised patients with IBD significantly increased from the years 2000 to 2018 30 . Despite publication of these guidelines, prior data from Manitoba suggest similar findings, noting a persistently high rate of VTE among patients with IBD 14 . When restricting our analysis to only include admissions from the ER with a primary indication of IBD, although the rates of VTE did not increase, they remained persistently elevated over time.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Given the theoretical risk of suboptimal immune responses on the one hand and an apparently higher effectiveness of mRNA-based vaccines, there could be a rationale for a preferred use of these vaccines in IBD patients. Additionally, IBD patients are typically of a younger age and carry an increased risk for venous thromboembolism due to their underlying disease [40][41][42]. After the approval of the vector vaccines ChAdOx1 and Ad26.CoV2.S and application to millions of people, rare but significantly increased cases of cerebral thrombosis were detected especially in recipients of a younger age, while this was not the case after vaccination with mRNA vaccines [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, patients with chronic inflammatory diseases, such as systemic lupus erythematosus, rheumatoid arthritis, and psoriasis, have an increased risk of arterial and venous thromboembolic events [ 4 ]. Population-based studies have also suggested that patients with inflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn’s disease (CD), might be at an increased risk for CVDs, including coronary artery disease (CAD) and arterial and venous thromboembolic events [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%